Bullous striae distensae in a young patient with cardiomyopathy (Dermatology Reports, 2023)
Striae distensae (SD), also known as stretch marks, are observable linear scars that appear where dermal damage has occurred as a result of prolonged stretching of the skin. The actual pathophysiology of SD is still up for debate because its origins are multifaceted. Generally, striae are benign lesions, but larger lesions may get traumatized and become ulcerated or rupture. In patients with edema and receiving systemic steroids, bullous SD could develop secondary to fluid buildup preferentially in striae. We report a case of a young patient with cardiomyopathy who received systemic steroids and developed bullous striae distensae.